An Analysis Of Giant's Competitive Advantage In Singapore - Jesbir Singh, Suneeta Kaur (2009)
The research is motivated by the entry of Giant hypermarket into Singapore Market. The objectives of this study are to analyze the global marketing strategies used by Giant and to determine if Giant is able to adapt and use its core competencies to create competitive advantage in singaporeas it has successfully done in other countries.